Method of Systematizing the European Union States in Categories According to their Administrative Capacity - Irina Bosie (CES Working Papers, 2012)
During times of severe budget reductions and limitations, it becomes necessary to conduct an evaluation of the ability of the States to carry out the administrative process and to provide useful solutions developed through common policies at European level, necessary for costs abatement, towards maintaing the productivity and the innovative potential of organizations and in order to secure employment. Evaluation at the European Union level is essential to the identification of the weak elements for each state and in order to effectively provide a broad palette of services focused towards the citizens. The idea of developing an evaluation system was instituted after the establishment of a common framework of quantitative assessment, Common Assessment Framework (CAF). CAF is a tool used to help public sector organizations in Europe in the use of quality management techniques sintended to improve performance. This tool wants to be a global tool for comparative analysis of administrative performance. As described on the official website of the program, the model is based on the premise that excellent results of organizational performance, of the citizens/customers and of the society are achieved through leadership and planning strategy, people, partnerships, resources and processes. At the end of the research, the analysis of the main components will confirm the results, shown by European Union States progress in sustainable development of public sector.
Keywords: H4; F3; D73; 330; administrative capacity; decentralization; public services development; sector public progress Romania